Controlling Corruption Through Integrity Committees: The Case of Zambia. (4th May 2019) - Hope, Kempe Ronald
Abstract : This work discusses and evaluates Zambia's Integrity Committees Program, which is being implemented by the country's Anti-Corruption Commission, as a framework for corruption control. The Integrity Committees Program in Zambia has garnered considerable support and adoption from employees in both the public and private sectors and also has support from the highest levels of government. Notwithstanding some of the challenges it has encountered, its implementation can be generally regarded as successful, and offers lessons of experience for African and other developing countries implementing similar programs or intending to do so. Based on an analysis of credible governance data, national surveys, policy documents, and available relevant literature, the work traces the measured perceptions, extent, and nature of corruption in Zambia and the introduction and impact of the Integrity Committees Program as a response mechanism to reduce and control that corruption. The work indicates that although there has been an improvement in the corruption environment in Zambia, corruption is still a problem in the country. Nevertheless, there can be no doubt that much has changed in the country in terms of its corruption reputation since the 1980s, 1990s, and early 2000s when even donors froze funding due to corruption concerns.